2008
DOI: 10.1038/sj.bjc.6604279
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of FOXO1 in cytotoxic stress and drug-resistance induced by paclitaxel in ovarian cancers

Abstract: The role of transcriptional factor FOXO1 in the mechanism of drug-resistance in ovarian cancer has not been elucidated. In ovarian cancer cell lines, FOXO1 expression and its correlation with paclitaxel treatment was investigated by cytotoxic assay and silencing experiment. Clinical ovarian cancer samples were also examined for FOXO1 expression by immunohistochemistry. FOXO1 expression was distinctively upregulated in paclitaxel-resistant cell line, and enhanced by exposure to paclitaxel. FOXO1 overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported. In the present study, we used two gastric cancer cell lines, MKN45 and SNU-601, with constitutive FOXO1 expression and found that CDDP treatment increased the levels of FOXO1 protein expression and activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported. In the present study, we used two gastric cancer cell lines, MKN45 and SNU-601, with constitutive FOXO1 expression and found that CDDP treatment increased the levels of FOXO1 protein expression and activation.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 increased doxorubicin resistance in breast cancer cells [8] and paclitaxel resistance in ovarian cancer cells [9], whereas it decreased CDDP resistance in ovarian cancer cells [10]. Thus, the effect of FOXO1 on the chemoresistance of cancer cells may differ according to the drug and cell type investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cell death occurs, it takes place mainly via the intrinsic pathway of apoptosis. Among the apoptotic events initiated by paclitaxel, there have been included several modifications of Bcl-2 family proteins such as Bcl-2 and Bcl-xL phosphorylation, Bax activation (2,5), or Bim induction by Forkhead box O (FoxO) transcription factors (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation and inactivation of forkhead box protein O1 (FOXO1) is an important mechanism by which Akt activation promotes cell survival (Rena et al, 1999). FOXO1 acts as a tumor suppressor in a variety of cancers including ovarian cancer (Goto et al, 2008;Xie et al, 2012). Several studies have demonstrated that the anticancer effect of curcumin is associated with the modulation of FOXO1 expression (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%